Phytochemical, Analgesic And Acute Toxicity Studies Of Uncaria Attenuata (Korth.) Leaf Extract - Ga, Tan Ai Fein A/p Ching (2023)
Uncaria species from the family of Rubiaceae is a type of climbing vine found across Southeast Asia, East Asia, and South America. The Uncaria leaves and hooks (claw-like) traditionally been used to treat pain, neurological disorders, hypertension, stroke, rheumatism and other ailments. The study aimed to extract, isolate, and characterize the alkaloid constituents from the leaves of Uncaria attenuata (Korth.). In the present study, female Sprague Dawley rats were evaluated for acute toxicity for 14 days. In order to evaluate the antinociceptive activity of U. attenuata extracts and isolated alkaloid, a rat hot plate model was carried out. Two alkaloids have been successfully isolated and purified using chromatographic techniques: column chromatography, thin-layer chromatography and preparative thin-layer chromatography. Structure elucidation was performed using 1D NMR (1H, 13C, DEPT 90, DEPT 135), 2D NMR (COSY, HMBC, HSQC and NOESY), UV-Vis, FTIR, GC-MS and LC-MS. For the acute toxicity study, the rats were fed orally and employed in series of 175, 550 and 2000 mg/kg following the OECD 425 guideline. The rats were evaluated for physical abnormalities, infection, differences in posture and movement, and mortality. The relative organ weight of the rats’ harvested organs was calculated. Subsequently, for the analgesic study, the methanolic extract (250, 500 mg/kg), alkaloid extract (50, 100 mg/kg), and villocarine A (5, 10, 20 mg/kg) were given orally to the rats, respectively.